2019
DOI: 10.1007/s10943-019-00845-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Religiosity and Spirituality in the Sexual Decision-Making of Black Gay and Bisexual Men

Abstract: Many Black gay and bisexual men (BGBM) practice consistent religious worship and spirituality in order to cope with social challenges. This study utilized data from in-depth qualitative interviews conducted to explore personal meanings of religiosity and spirituality and how these constructs affect partner choices and sexual behaviors among BGBM. Interviews were conducted with 26 BGBM in Los Angeles, California, from September to November 2015. In-depth interviews yielded themes related to BGBM's understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 39 publications
0
34
0
1
Order By: Relevance
“…not been widely explored to improve the health of individuals with HIV among MSM. 13 Based on the background, it was found that the behavior of condom use by MSM was related to self-belief and spirituality. It was found that there was a role for self-efficacy and spirituality in MSM.…”
Section: Significance For Public Healthmentioning
confidence: 99%
“…not been widely explored to improve the health of individuals with HIV among MSM. 13 Based on the background, it was found that the behavior of condom use by MSM was related to self-belief and spirituality. It was found that there was a role for self-efficacy and spirituality in MSM.…”
Section: Significance For Public Healthmentioning
confidence: 99%
“…Historically, Christianity has been an integral institution within the African American community, and relationships with fellow churchgoers could serve as a source of social support and belongingness for African American SMM. Research has shown that many African-American SMM use religious and spiritual practices to cope with daily social stressors (Dangerfield et al, 2019). This protective effect has also been demonstrated among Nigerian SMM whereby religiosity was associated with better quality of life and, along with other adaptive coping strategies, attenuated the association between internalized homophobia and quality of life (Oginni et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…However, many SMM struggle with balancing their religious/spiritual beliefs with their same-sex attractions, sexual orientation, and sexual practices. Specifically, (Dangerfield et al, 2019) found that African American SMM reported struggling with feelings of internalized homonegativity due to being raised in the church and being constantly confronted with negative messages about samegender attractions. This demonstrates the complexities and complications that comes with balancing one's religious identity with being part of a sexual minority group.…”
Section: Introductionmentioning
confidence: 99%
“…Spirituality and religion are salient among Black SMM [10,11]. Black SMM are more likely to report spirituality and religion as very important to them compared to other racial/ethnic groups of sexual minority men [12].…”
mentioning
confidence: 99%
“…However, studies have demonstrated a paradox of spirituality and religiosity being associated with both risk for and protection against HIV among Black SMM [11,[19][20][21][22]. Spirituality and religiosity have been associated with HIV and other sexually transmitted infections [21,23,24], lower gay affirmation [25], and with high-risk behaviors such as illicit drug use and increased number of partners [21,22].…”
mentioning
confidence: 99%